(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
A transdiagnostic hypothesis arisen from the contextual therapies, specifically from the Functional Analytic Psychotherapy (FAP) is presented. According to it there would be common problems in many psychopathological disorders in the form of problems in the formation of the Self. For FAP the Self is a concept learned through verbal and social context; it is a generalization learned in a very early age from phrases that include I as active subject, as a place or a perspective from the one it is operated. FAP considers that the degree of private and/or public control in this learning of Self may lead to slight or serious problems, because this concept of Self has been reinforced and supported by the social context. We describe the theory about how the Self would be formed verbally and socially through different stages, as well as the diverse types of psychological problems that can be developed in such way. Finally, FAP’s assessment and intervention in these problems of Self, specially the personality disorders, are described. We conclude mentioning that it is necessary to research and test this hypothesis in clinical cases or in analogous studies.